Development of E-Outing System (EOS) using adapted prototype model / Norarina Ezzati Johan, Nor Azila Awang Abu Bakar and Nik Marsyahariani Nik Daud - Johan, Norarina Ezzati; Awang Abu Bakar, Nor Azila; Nik Daud, Nik Marsyahariani (2016)
The application of automated systems is widely used in information management process in this era. This paper observes on the application of automated system in managing information by using a case study. The case study has been conducted at Sekolah Menengah Sains Dungun (SMSD), specifically within their hostel management system. The school management currently use manual process in order to collect and record information on outing. E-Outing System (EOS) is proposed to facilitate the school outing record management. EOS is developed using adapted Prototype Model that includes requirement gathering phase, quick design phase, prototype development phase, user evaluation phase, refining prototype and engineer product phase. Based on the final product, user acceptance test is conducted where the result showed that the system enables the school management to improve their management process. Respondents are mostly satisfied with user interface as it scores the highest mean with 4.33 (SD=0.61) out of 5. Overall result concludes that EOS improves the current process.